Ultrathin Li4Ti5O12 Nanosheet Based Hierarchical Microspheres for High‐Rate and Long‐Cycle Life Li‐Ion Batteries. Issue 21 (19th July 2017) - He, Yishi; Muhetaer, Aidaer; Li, Jianming; Wang, Feifan; Liu, Cheng; Li, Qi; Xu, Dongsheng
Abstract: Ultrathin Li4 Ti5 O12 nanosheet based hierarchical microspheres are synthesized through a three‐step hydrothermal procedure. The average thickness of the Li4 Ti5 O12 sheets is only ≈(6.6 ± 0.25) nm and the specific surface area of the sample is 178 m 2 g −1 . When applied into lithium ion batteries as anode materials, the hierarchical Li4 Ti5 O12 microspheres exhibit high specific capacities at high rates (156 mA h g −1 at 20 C, 150 mA h g −1 at 50 C) and maintain a capacity of 126 mA h g −1 after 3000 cycles at 20 C. The results clearly suggest that the utility of hierarchical structures based on ultrathin nanosheets can promote the lithium insertion/extraction reactions in Li4 Ti5 O12 . The obtained hierarchical Li4 Ti5 O12 with ultrathin nanosheets and large specific surface area can be perfect anode materials for the lithium ion batteries applied in high power facilities, such as electric vehicles and hybrid electric vehicles. Abstract : Ultrathin Li4 Ti5 O12 nanosheet based hierarchical microspheres demonstrate enhanced rate performance and long cycle life when used in lithium ion batteries as anode materials. The excellent electrochemical performance can be ascribed to the reduced transport path lengths of lithium ions/electrons and the increased electrode/electrolyte interfaces, which are derived from the unique hierarchical structure.